DETERMINATION OF POPULATION DYNAMICS OF PSEUDOMONAS FLUORESCENS IN THE SOIL PLANTED WITH TOMATO GROWN ON DE-OILED CAKES OF MAHUA AND KARANJA - MANOJ KUMAR MAURYA; RAMJI SINGH; AJAY TOMER (The Bioscan, 2014)
The main aim of this study was to determine the effect of de-oiled mahua and karanja cakes on the population dynamics of Pseudomonas fluorescens. We also made different combination of these de-oiled cakes and P. fluorescens with soil and check their effects on the tomato plant. We made 7 treatments and found that highest recovery of P. fluorescens on mixture of mahua and karanja cakes in sterilized soil (230×108cfus at 60 DAP) and unsterilized soil (215×108cfus at 60 DAP) when this mixture was used for cultivation of tomato plants. It shows the most promising effects on the tomato plant. It has beenalso found during this study that Shelf life of P. fluorescens was also high(120 days) in the above said treatment.From the above results it is clear that both the de- oiled cakes have profound effect on the population dynamics and shelf life of P. fluoresces which in turn enhance tomato plants root length (70.00%), shoot length (72.28%) and yield (541.65%). Thus we can say that these agro wastes can be used as carrier material for the growth and mass multiplication of P. fluorescens.